2014
DOI: 10.1093/nar/gku1107
|View full text |Cite
|
Sign up to set email alerts
|

Ion distributions around left- and right-handed DNA and RNA duplexes: a comparative study

Abstract: The ion atmosphere around nucleic acids is an integral part of their solvated structure. However, detailed aspects of the ionic distribution are difficult to probe experimentally, and comparative studies for different structures of the same sequence are almost non-existent. Here, we have used large-scale molecular dynamics simulations to perform a comparative study of the ion distribution around (5′-CGCGCGCGCGCG-3′)2 dodecamers in solution in B-DNA, A-RNA, Z-DNA and Z-RNA forms. The CG sequence is very sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 123 publications
(130 reference statements)
5
60
1
Order By: Relevance
“…We observed that dsRNA attracts more monovalent cations than dsDNA and interacts more favourably with Mg 2+ . These results indicate that the electrostatic field around the RNA duplex is stronger than that of the DNA duplex, as proposed by numerous computational studies (34)(35)(36)(37)(38)(39)65).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We observed that dsRNA attracts more monovalent cations than dsDNA and interacts more favourably with Mg 2+ . These results indicate that the electrostatic field around the RNA duplex is stronger than that of the DNA duplex, as proposed by numerous computational studies (34)(35)(36)(37)(38)(39)65).…”
Section: Discussionsupporting
confidence: 71%
“…Yet, our knowledge of the ion atmosphere around RNA helices is limited. There are several computational studies dedicated to quantifying the RNA-ion interactions within the ion atmosphere (34)(35)(36)(37)(38)(39)(40); in particular, Poisson-Boltzmann (PB) calculations have emerged as the approach of choice, in part because it is easily implementable, computationally tractable, and conceptually straightforward (41)(42)(43)(44)(45)(46). However, there are few experimental studies on the RNA electrostatics, and the complex RNAs used typically prevents isolating and dissecting the ion atmosphere and its associated energetics (41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Introductionmentioning
confidence: 99%
“…A Na + ion can stabilize a G-G mismatch by forming an ion bridge connecting the G(O6) atoms in the four G bases in a double G-G mismatch (Figure 12a); or the two bases in a single G-G mismatch and the two bases in the adjacent G-C base pair (Figure 12b). These pockets are very similar to the Na + ion trapped in a (CG) 6 duplex, where the ion is held by two G(O6) and two C(N4), in both B-DNA and A-RNA (see Figure 14a and b in ref 22). …”
Section: Resultsmentioning
confidence: 67%
“…Figures S11 and S12 show the neutralizing Na + ion occupation as a function of base pairs in the major and minor grooves, and Figure 12 shows some typical patterns for ions involved in direct binding to the mismatched bases. We know from studies of ion distributions in the sequence (CG) 6 22 that neutralizing Na + ions sit preferentially around the G bases in the major grooves, both in B-DNA and A-RNA forms. This trend is clearly seen in the G-rich duplexes in Figures S11 and S12 where the amount of ions in the minor groove is completely negligible and most of them sit in the major groove, especially around the G-G mismatches.…”
Section: Resultsmentioning
confidence: 99%
“…2733 These simulations typically reveal cations in helical grooves, with a size dependence to this occupancy, 29,31,32,3439 and greater accumulation of smaller cations around phosphoryl oxygen atoms. 30,31,37,40,41 Thus, computational approaches have provided general support for cation size as an important determinant of cation position in and occupancy of the ion atmosphere and of the ion atmosphere’s ability to screen nucleic acid charge.…”
Section: Introductionmentioning
confidence: 99%